Strategi Branding Sekolah Dalam Meningkatkan Awereness Masyarakat - Yekti Azizah; Umi Halwati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This study aims dig deeper into school branding strategies in increasing public awareness. The research method used is a qualitative method focusing on library research. The results of research on school branding strategies in increasing public awareness include (1) cool school uniforms, (2) forming positive characteristics that are superior and proud of, (3) realizing both academic and non-academic achievements, interesting documentation and publications, (4) visual documentation accompanied by written documentation with an attractive design, (5) utilization of information technology, (6) formation of a good slogan or take, (7) creating valued alumni.